Novel Nano Zn+2-Compound from LA Ligand as an Acid-Base Indicator: Synthesis, Characterization, pH Sensor, and Fluorescent Study - AL-Qaysi, Wafaa Waleed; Abbas, Alyaa Khider (Iraqi Journal of Science, 2023)
The main goal of our research is to synthesize novel nano Zn2+ complex with the 8-(2-(dansyl chloride)azo) adenine (LA) ligand as a pH sensor because of its advantageous properties, obtained from a single molecule. The Zn2⁺- LA complex was based on the production of an intensely dark purple-colored substance with λmax at 552 nm. Molar ratio of Zn2⁺- LA complex is a 1:2 in aqueous buffer. The optimum concentration (0.3) mM, pH (2-5.5), and time (0-3) hr at pH=5.5, that in the studies followed Lambert-law Beer’